PERANCANGAN SISTEM SORTING BUAH JERUK MANIS BERBASIS PERBEDAAN WARNA KULIT BUAH - Kurniawan, Edi (Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2015)
Almost all farmers use manual way to identify the level of maturity of oranges in doing the sorting. Identifying using the manual method has some drawbacks, namely the level of accuracy and farmers have already experience. With advances in technology now, sort of citrus fruits is based on the level of maturity can be done using digital image processing. Many digital image processing method one of them is the edge detection method. Edge detection method is used to determine the borders of an object. This study uses edge detection method to determine the extent of the orange color of the peel of citrus fruits because one of the characteristics of citrus fruit maturity level is how dominate the area of orange color on its peel. The results showed that with 10 oranges with a different maturity level, the system can determine it exactly. The average time required by the system to determine the level of maturity of citrus fruits is 0.6 secondsKeywords : citrus maturity, digital image processing, edge detection